PENGARUH JARAK TEMPAT TINGGAL PESERTA DIDIK TERHADAP KEAKTIFAN MENGIKUTI MATA PELAJARAN IPS DIKELAS VII SMP NEGERI 1 KASIMBAR KEC. KASIMBAR KAB. PARIGI MAUTONG - Nurjannah; Lisnawaty, Sri Dewi; Zaifullah, Zaifullah (Program Studi Tadris Ilmu Pengetahuan Sosial (TIPS) UIN Datokarama Palu, 2022)
The purpose of this study was to determine the effect of the distance where students live in their active participation in social studies subjects in Class VII SMP Negeri 1 Kasimbar Kec. Kasimbar Kab. Parigi Mautong. This study uses a quantitative approach Expo facto. Data collection techniques using a questionnaire (questionnaire) and sampling using the Slovin formula (Stratifite Random Sampling) while the sample used in this study was 60 students of class VII.) The technique of Simple Linear Regression Analysis. The results show that the effect of the distance from which students live on their active participation in social studies subjects can be seen from the statistical test results obtained t_count > t_table or 28,229>2,001, this means that the distance from which they live (X) has a significant effect on their active participation in subjects Social Studies (Y) with a large influence of 0.428 or 43% based on this result the distance of the students' residence to their active participation in Social Studies subjects in Class VII SMP Negeri I Kasimbar Kec. Kasimbar Kab. Parigi Mautong is quite high. The implication of the research is that teachers are expected to be able to try to maintain and increase the learning activity of students in social studies subjects in class VII SMP Negeri 1 Kasimbar